2007
DOI: 10.1007/s10535-007-0111-z
|View full text |Cite
|
Sign up to set email alerts
|

Direct plant regeneration from cucumber embryonal axis

Abstract: Embryonal axis explants from 2-d-old in vitro germinated seeds were used to induce multiple shoot production. The combination of 4.44 µM BA and 1.59 µM NAA in MS medium triggered the initiation of adventitious shoot buds. The explants with shoot buds produced maximum number of shoots (10.6 per explant) in MS medium supplemented with 4.44 µM BA and 0.065 mM L-glutamine in three successive transfers. The elongated shoots were rooted on MS medium with 4.92 µM IBA. Rooted plants were transferred to soil with a sur… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
17
0

Year Published

2008
2008
2018
2018

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 15 publications
(18 citation statements)
references
References 14 publications
1
17
0
Order By: Relevance
“…In bottle gourd, AgNO 3 (an ethylene inhibitor) is able to promote shoot regeneration from proximal cotyledon explants 9 . Addition of cytokinins to culture media has been reported to be crucial for the induction of adventitious shoot and proliferation in vitro shoot regeneration of numerous Cucurbitaceae such as cucumber, bottle gourd, squashes, and a Cucurbita interspecific hybrid 3,[7][8][9][18][19][20] . Cytokinin can be used alone or in combination with a low concentration of auxins 4,5,14 .…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…In bottle gourd, AgNO 3 (an ethylene inhibitor) is able to promote shoot regeneration from proximal cotyledon explants 9 . Addition of cytokinins to culture media has been reported to be crucial for the induction of adventitious shoot and proliferation in vitro shoot regeneration of numerous Cucurbitaceae such as cucumber, bottle gourd, squashes, and a Cucurbita interspecific hybrid 3,[7][8][9][18][19][20] . Cytokinin can be used alone or in combination with a low concentration of auxins 4,5,14 .…”
Section: Discussionmentioning
confidence: 99%
“…An important prerequisite for a successful plant transformation is the development of a yet unavailable efficient plant regeneration system in vitro for chieh-qua 1 . Up to now, there have been a number of studies on in vitro regeneration of several Cucurbitaceae crops including cucumber 2,3 , watermelon 4,5 , melon 6 , squash 7,8 , bottle gourd 9 , figleaf gourd 10 , ash gourd 11 , muskmelon 12 , and chieh-qua 1 . However, only in cucumber, watermelon, squash, and melon, efficient and reliable plant regeneration protocols have been established.…”
Section: Introductionmentioning
confidence: 99%
“…Thomas and Sreejesh (2004) have reported that the addition of 0.2 μM NAA with 4 μM 6-benzylaminopurine (BAP) was beneficial for adventitious shoot regeneration in the cotyledon-derived callus of ash gourd. When compared with cucumber (Vasudevan et al, 2004;Vasudevan et al, 2007b), watermelon (Sultana and Bari, 2003;Sultana et al, 2004), melon (Curuk et al, 2002;Muruganantham et al, 2002) and squash (Ananthakrishnan et al, 2003;Kathiravan et al, 2006), chieh-qua also needed a high concentration of 6-BA for shoot induction. Such a high concentration may influence shoot proliferation as well as elongation, and could be one of the reasons for the difficulty of regeneration of chieh-qua.…”
Section: Discussionmentioning
confidence: 99%
“…Up to now, some efficient plant regeneration protocol has been established in some crops of Cucurbitaceae (Chaturvedi and Bhatnagar, 2001;Soniya and Das 2002;Kintzios et al, 2002;Curuk et al, 2002;Lee et al, 2003;Ananthakrishnan et al, 2003;Sultana et al, 2004;Akasaka-Kennedy et al, 2004;Thomas and Sreejesh, 2004;Kathiravan et al, 2006;Selvaraj et al, 2007;Vasudevan et al, 2007a;Suratman et al, 2010). However, the regeneration of Cucurbitaceae crops is not accomplished like other model plants.…”
Section: Introductionmentioning
confidence: 99%
“…immature embryos. Vasudevan et al 2007 reported positive effects of BA and α-naphthaleneacetic acid (NAA) on the cucumber regeneration from embryonal axis. Table 1.…”
Section: ⎯⎯⎯⎯mentioning
confidence: 99%